Pro iOS Security and Forensics Enterprise iPhone and iPad Safety - Butow, Eric (Apress, 2018)
Examine how to keep iOS devices safe in the physical world, including creating company policies for iPhones; assessing and defending against cyber vulnerabilities and attacks; working with preinstalled as well as third party tools; and strategies for keeping your data safe including backing up and screen locks. Managing and maintaining iPhones and iPads in a corporate or other business environment inherently requires strict attention to security concerns. Managers and IT professionals need to know how to create and communicate business policies for using iOS devices in the workplace, and implement security and forensics tools to manage and protect them. The iPhone and iPad are both widely used across businesses from Fortune 500 companies down to garage start-ups. All of these devices must have secure and monitorable ways to connect to the internet, store and transmit data without leaks, and even be managed in the event of a physical theft. Pro iOS Security and Forensics covers all these concerns as well as also offering tips for communicating with employees about the policies your business puts in place, why those policies are important, and how to follow them.